Direct Electrochemical Deposition of Lithium from Lithium Oxide in a Highly Stable Aluminium‐Containing Solvate Ionic Liquid. Issue 22 (3rd September 2018) - Zhang, Baoguo; Yao, Yu; Shi, Zhongning; Xu, Junli; Wang, Zhaowen
Abstract: Low‐temperature electrochemical extraction of active metals from their corresponding chlorides in ionic liquids has long been a scientific challenge, while extraction from oxides is even more difficult. Inspired by previous reports of the electrochemical deposition of various non‐active metals from their corresponding oxides in diverse ionic liquids, we demonstrate the successful electrodeposition of active Li on high‐purity Al‐plate substrates at relatively low temperature (353 K), as confirmed by X‐ray diffraction. Furthermore, Al−Li alloy nanosheets can also be obtained on the Al surface by solid‐state cathode alloying. The Li source was Li2 O, which was dissolved in a highly stable Al‐containing solvate ionic liquid. The dissolution mechanism and electrodeposition behaviour of Li2 O were investigated using multinuclear nuclear magnetic resonance spectroscopy, theoretical calculations, and electrochemical techniques. The findings are expected to provide a theoretical basis and method for low‐temperature electrochemical extraction of active metals from their oxides. Abstract : Active metal extraction : Li2 O is employed as the precursor for Li extraction and dissolved in an electrochemically stabilized Al‐containing solvate ionic liquid. Direct electrochemical deposition of Li from Li2 O is achieved at a relatively low temperature. Al−Li alloy nanosheets can also be obtained on the Al surface. The dissolution mechanism provides guidance for identifying species with stronger Lewis acidity to combine with other active metal oxides.